Analisis Kelayakan Usahatani Tebu Bongkar Ratoon (Studi Kasus Petani Tebu di Kecamatan Pagu) - Fitranto, Deyon Yanuar; Roidah, Ida Syamsu; Harya, Gyska Indah (Universitas Galuh, 2024)
Sugar cane is a commodity that is rarely planted by farmers in Pagu District, Kediri Regency, even though it has profitable potential. By using the ratoon unloading technique, it is hoped that sugar cane farmers will get maximum profits. The aim of this research is to analyze the feasibility of farming, analyze the costs required by farmers, analyze the sensitivity of farming. The research method used was a survey method. The research location was chosen deliberately in Pagu District, Kediri Regency. Data was obtained from interviews with 30 sugar cane farmer respondents who used the ratoon unloading technique. The feasibility of unloading ratoon sugar cane farming was analyzed using Net Present Value (NPV), Internal Rate of Return (IRR), Benefit Cost Ratio (B/C), Payback Period (PP) and sensitivity analysis. The research results show that the NPV value is IDR. 142,229,960, IRR of 94%, Net B/C of 3.7, and PP of 1 year. Based on this analysis, the farming business is feasible to run. Based on the sensitivity analysis, ratoon unloading sugar cane farming is feasible if there is a 25% increase in fertilizer prices, a 3.25% increase in labor wages, a 25% increase in fertilizer prices and a 3.25% increase in labor wages.